Under-reporting of income by wealthy Indians - Singh,Ram and Ray, Soumyajit (Economic and Political Weekly)
The affluent Indians often complain about the (3z(Bexcessive(3y (Bincome taxation. Yet, very few of them figure among the top income taxpayers. This paradoxical situation results from the relatively low incomes reported by wealthy groups. On average, the wealthier a family is, the smaller the income it reports relative to its wealth.- Reproduced s